The archaeology of “celebrities” in the Greek and Roman worlds. - Jonathan M. Hall (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2019)
The debate about the identification of the house of Augustus on the Palatine hill or the controversy surrounding the occupant of Tomb 2 at Vergina or the recently excavated funerary complex at Amphipolis offers more than sufficient evidence for a public fascination with important historical personalities. Yet, at the same time, disciplinary trends in archaeology have sought to emancipate the material record from historicizing narratives and to occlude or decanter the knowing subject. The archaeology of the individual has become, at best, a quaint, antiquarian pursuit and, at worst, a celebration of neo-conservative ideology. This article will consider a series of case-studies from the ancient Greek and Roman worlds with the aim of illuminating the viability - and desirability - of practicing an archaeology of famous individuals.